Economic Assessment of Children’s Health and the Environment in Maine - Davis, Mary (Maine Policy Review, 2010)
Reducing children’s exposure to environmental toxins is important for both moral and economic reasons. Mary Davis discusses the economic impact of environmentally related childhood illnesses in Maine, focusing on disease categories with fairly strong evidence connecting environmental pollution to childhood diseases: lead poisoning, asthma, neurobehavioral disorders, and cancer. Lead poisoning and neurobehavioral conditions are the most expensive because they lead to chronic diseases that are largely incurable and not easily treated. She concludes that state funding for initiatives aimed at reducing childhood exposure to environmental pollutants “would be money well spent.”